2021
DOI: 10.1007/s12633-021-01030-6
|View full text |Cite
|
Sign up to set email alerts
|

A SiGe-Source Doping-Less Double-Gate Tunnel FET: Design and Analysis Based on Charge Plasma Technique with Enhanced Performance

Abstract: In this article, a distinctive charge plasma (CP) technique is employed to design two doping-less dual gate tunnel eld effect transistors (DL-DG-TFETs) with Si 0.5 Ge 0.5 and Si as source material. The CP methodology resolves the issues of random doping uctuation and doping activation. The analog and RF performance has been investigated for both the proposed devices i.e. Si 0.5 Ge 0.5 source DL-DG-TFET and Si-source DL-DG-TFET in terms of drive current, transconductance, cut-off frequency. In addition, the lin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 27 publications
(20 reference statements)
0
9
0
Order By: Relevance
“…The usage of SiGe alloy (Si 1-x Ge x ) as source material in TFET has also gained a lot of research interest because of improved synthesis techniques, ease of manufacturing, and bandgap energy control. [24][25][26][27] In this work, we propose a new n-type charge plasma TFET with Si 0.6 Ge 0.4 source pocket (SP-CPTFET) as a hydrogen gas sensor and compared it with the conventional CPTFET. The presence of a lowbandgap SiGe as a pocket in the vicinity of the source/channel interface offers a significant improvement in drain current and provides better sensitivity towards hydrogen gas.…”
mentioning
confidence: 99%
“…The usage of SiGe alloy (Si 1-x Ge x ) as source material in TFET has also gained a lot of research interest because of improved synthesis techniques, ease of manufacturing, and bandgap energy control. [24][25][26][27] In this work, we propose a new n-type charge plasma TFET with Si 0.6 Ge 0.4 source pocket (SP-CPTFET) as a hydrogen gas sensor and compared it with the conventional CPTFET. The presence of a lowbandgap SiGe as a pocket in the vicinity of the source/channel interface offers a significant improvement in drain current and provides better sensitivity towards hydrogen gas.…”
mentioning
confidence: 99%
“…where T Si is the silicon film thickness and T ox is the oxide thickness. We choose a diameter of 5 nm for our model [13] that provides us with the optimum results discussed in the results and analysis section. Further scrutinizing, we observed that the cylindrical construction leads to a greater density of tangential equipotential lines closer to the source.…”
Section: Device Dimensionsmentioning
confidence: 99%
“…As the temperature increases, the cut-off frequency decreases due to an increase in gate-gate capacitance and a decrease in g m . RF and analog metrics evaluated to determine device performance are mentioned below from equations (1) to (5) [21,22]: Figure 10 shows the output conductance (g d ) variation with temperature for D4 device. g d is used to determine the driving ability of the device.…”
Section: Rf Analysismentioning
confidence: 99%